Does digital economy development reduce carbon emission intensity? - Lyu, Yanfang; Zhang, Leifeng; Wang, Dong (Frontiers in Ecology and Evolution, 2023)
Carbon emissions from human activities are the main cause of climate warming. Under the background of economic and social digital transformation, accurately assessing the carbon emission reduction effect of the development of the digital economy is of great significance for countries to deal with climate warming in the post-Covid-19 era. This paper constructs a dynamic evaluation model of orthogonal projection to measure the level of digital economy development at the provincial level in China from 2013 to 2019. On this basis, the panel fixed effect model and mediation model are used to empirically test the impact of digital economy development on carbon emission intensity and its mechanism. The results indicate that: (1) The development of China’s digital economy is unbalanced among regions, showing a geospatial pattern of decreasing from east to west. (2) China’s carbon emission intensity has a trend of decreasing year by year, and there are geospatial differences of “high in the west and low in the east” and “high in the north and low in the south”. (3) The digital economy development can effectively reduce regional carbon emission intensity, but there is regional heterogeneity. The development of digital economy has a greater impact on carbon emission intensity in the middle and western regions, as well as in underdeveloped regions. (4) The digital economy development can reduce the carbon emission intensity through optimizing industrial structure and allocating resources more efficiently. This paper provides enlightenment for policy makers to deal with climate warming.